Implementasi Kode Etik Guru dalam Membentuk Karakter Siswa dan Pengaruhnya terhadap Hasil Belajar Siswa - Lamapaha, Ermelinda; Bhoki, Hermania; Keban, Yosep Belen (Vocat : Jurnal Pendidikan Katolik, 2024)
This research specifically investigates how the implementation of the teacher’s code of ethics shapes student’s character and influences the academic achievements of students at Hinga Catholic Elementary School. The benefits of this research are that it can serve as a reference for future research and provide information regarding the implementation of the teacher’s code of ethics in shaping students’ character and its impact on academic achievements. A qualitative descriptive approach was used in this research. This study was conducted at Hinga Catholic Elementary School involving four key informants who were directly involved in the learning process. The research was conducted for 3 months, from February to April 2024. Data were collected through in-depth interviews, participant observation, and document analysis. Data analysis was conducted systematically using a qualitative data analysis model. The research results indicate a positive correlation between the application of the teacher’s code of ethics is crucial in efforts to develop students with noble character and high achievements. The results of this study are expected to the development of educational science, especially in the field of character education.